An Empirical Analysis of the Relationship Between the Omega Ratio and Yield Skewness in European Government Bonds - Attila Bányai; Tibor Tatay; Gergő Thalmeiner; László Pataki (Emerging Science Journal, 2026)
This study examines the empirical relationship between the Omega ratio and yield skewness in European sovereign bond markets, addressing whether distributional asymmetry is systematically reflected in Omega-based performance evaluation. The analysis is guided by two research questions: whether a statistically significant association exists between the Omega ratio and yield skewness across different time horizons, and whether this relationship exhibits cross-country heterogeneity consistent with a core–periphery structure. Using daily data for 10-year government bonds from 27 European countries over the period 2015–2025, we construct constant-maturity total returns and apply a robust Omega ratio formulation with inflation-adjusted thresholds. Yield skewness is measured using time-adjusted daily yield changes. The empirical strategy combines rolling-window correlation analysis, hierarchical clustering based on Kendall’s τ, and Independent Component Analysis to capture both short-term dynamics and latent structural patterns. The results provide strong and consistent evidence of a significant relationship between the Omega ratio and yield skewness across short-, medium-, and long-term horizons, confirming that the Omega ratio captures meaningful aspects of return asymmetry in fixed-income markets. Importantly, the findings reveal pronounced regional heterogeneity: core and Northern European markets exhibit stable positive associations, while several peripheral and emerging markets display weaker or negative relationships. These results imply that Omega-based performance measures reflect not only statistical asymmetry but also underlying differences in market liquidity, risk premia, and institutional structure. Overall, the study highlights the relevance of distribution-sensitive performance measures for sovereign bond evaluation and contributes novel evidence from the European fixed-income context.